AB0212 LONG-TERM TREATMENT WITH RITUXIMAB IN SYSTEMIC SCLEROSISMANAGEMENT: AN OVERVIEW OF THE CLINICAL EXPERIENCE FROM A REAL-LIFE SETTING. (June 2019) - Lumetti, Federica; Spinella, Amelia; Colaci, Michele; Cocchiara, Emanuele; Magnani, Luca; Baiocchi, Gianluigi; Ferri, Clodoveo; Salvarani, Carlo; Giuggioli, Dilia
Abstract : Background: The treatment of systemic sclerosis (SSc) is a clinical challenge because of its complex pathogenesis. The rationale for the use of rituximab (RTX), able to downregulate the B-cell over expression, is demonstrated in different autoimmune diseases, some reports have suggested its key role in regulating both vascular, fibrotic, and immune T- and B-lymphocyte-mediated alterations that characterize several SSc manifestations. According to our previous experience with RTX [1], we suggested a possible therapeutical role of RTX in SSc, along with its good safety profile. Objectives: To investigate the role and efficacy of RTX in our SSc patients' series. Methods: A series of 24 SSc patients (M/F 7/17, mean age 55.2±14.7SD years, mean disease duration 11.7± 7.3SD years, L/D cutaneous subsets 11/13) were treated with one or more cycles of RTX (4 weekly infusions of 375 mg/m 2 ) and evaluated during a mean follow-up period of 12.3 ± 6.6SD years, range 2-26 years. The indications to RTX were interstitial lung disease, cutaneous, articular manifestations, evaluating its effects after 6 months of the first cycle and at the end of follow-up. Results: After the first 6 months the extent of skin sclerosis measured with modified Rodnan skin score (mRSS) significantly improved (from 16.3±9.8 to 12.3±7.1; p<0.0001), and remained stable at the end of the follow-up (11.0±6.9; p=0.105). The effect on skin sclerosis was more evident in patients with diffuse cutaneous SSc (n=13) showing a significant decrease of mRSS after the first 6 months (from 24.3± 5.4 to 17.9±4.3; p=0.006) and at the end of the follow-up period (17.8±5.7; p=0.005). Similarly, a valuable improvement of other skin manifestations, namely hypermelanosis (17/20 pts), pruritus (18/21 pts), digital ulcers (8/18 pts) and calcinosis (6/3 pts), was observed. Moreover, arthritis revealed a good response to RTX treatment leading to a clear-cut reduction of swollen (from 2.0±2.8 to 0.3±1.3; p<0.0001) and tender joints (from 5.2±4.0 to 0.9±2.5; p<0.0001) in 20/24 patients. Finally, lung fibrosis detected in 19/24 on chest-CT remained stable during the entire follow-up, as well as pulmonary function tests (PFTs). These positive clinical changes were mirrored by the subjective improvement of patients' well being in all subjects (HAQ from 1.04±0.55 to 0.85±0.38; VAS from 71.0±15.2 to 28.0±10.3, p<0.0001). No significant side effects were observed during the entire follow-up. Only in one patient a severe urinary tract infection leading to the discontinuation of the treatment was detected. Conclusion: The present study reinforces the previous trials and our preliminary researches on this topic, showing the efficacy of RTX in the management of SSc with good safety profile. The specific therapeutical role of RTX on B-cell-driven autoimmunity, might explain its beneficial effects on some SSc clinical alterations. The improvement of skin sclerosis, articular symptoms and the stabilization of lung involvement were identified as the main results. Further exploration of the potential clinical efficacy of RTX in SSc with multicentre, double blind, controlled study is needed. Reference: [1] Giuggioli D, et al. Rituximab in the treatment of patients with systemic sclerosis. Our experience and review of the literature. Autoimmun Rev. 2015;14(11):1072-8 Disclosure of Interests: None declared